Afterword: On Racial Binaries, Racism, and Creolization. Issue 1 (1st June 2021) - Dominguez, Virginia R.
Abstract : Author of the pathbreaking work on créolité in Louisiana, White by Definition: Social Classification in Creole Louisiana (1986), Virginia R. Dominguez responds to the articles presented in the special dossier, "Créolité: Identity, History, Culture/Kreyòl: métissage, hybridité, bricolage." Her reflections situate articles by Jonathan Gosnell, Juliane Braun, and Angel Adams Parham in relation to the racial binary dominating Anglo-American history in the U.S., racism (old and new), the relevance of history to the present, and writers' and intellectuals' roles in fostering change for the better. Auteur du texte fondateur sur la créolité en Louisiane, White by Definition: Social Classification in Creole Louisiana (1986), Virginia R. Dominguez répond aux articles présentés dans le dossier spécial, "Créolité: Identity, History, Culture/Kreyòl: métissage, hybridité, bricolage." Ses réflexions situent les articles de Jonathan Gosnell, Juliane Braun et Angel Adams Parham par rapport au binarisme racial qui domine l'histoire anglo-américaine dans les États-Unis, le racisme (ancien et nouveau), et la pertinence de l'histoire à l'actualité, ainsi que le rôle des écrivains et des intellectuels à travailler pour le changement.